Glycoprotein Non-Metastatic Protein B: an Emerging Biomarker for Lysosomal Dysfunction in Macrophages - van der Lienden, Martijn (2019)
Several diseases are caused by inherited defects in lysosomes, the so-called lysosomal storage disorders (LSDs). In some of these LSDs, tissue macrophages transform into prominent storage cells, as is the case in Gaucher disease. Here, macrophages become the characteristic Gaucher cells filled with lysosomes laden with glucosylceramide, because of their impaired enzymatic degradation. Biomarkers of Gaucher cells were actively searched, particularly after the development of costly therapies based on enzyme supplementation and substrate reduction. Proteins selectively expressed by storage macrophages and secreted into the circulation were identified, among which glycoprotein non-metastatic protein B (GPNMB). This review focusses on the emerging potential of GPNMB as a biomarker of stressed macrophages in LSDs as well as in acquired pathologies accompanied by an excessive lysosomal substrate load in macrophages.